Analysis of Indonesian Ship Accident 2005-2010 - Faturachman, Danny; Shariman, Mustafa (2012)
There are so many accident in sea transportation in Indonesia. Accidents occurring in rivers, lakes, and crossing that reached Marine Court in 2005-2010 is due to human error factor (65%), and only a few accidents in the waters caused by natural factors. Given the reasons mentioned above should all accidents can be minimized if prevention efforts from all parties so as not to stumble on the same stone. Most of the accidents happen because of low concern aspects of the safety and security of the crew. The numbers differ from the manifest of passengers and the number of passengers on the field became a regular thing going on. There are four main issues in maritime transport, i.e. no persons or Government agencies that are willing to hold the responsibility of safety and security, tariff policy, the quality of human resources, as well as the implementation and enforcement of the regulations is not clear. Safety of sea transportation should also start from the port conditions are sterile. The port is the main key from out the influx of sea transport. Unfortunately, almost all ports in Indonesia does not have any crossing facilities or equipment to control weight, dimensions, and other types of payloads in any vehicle that boarded the ship. It becomes a threat to the safety of shipping crossing, particularly if a malicious payload that went into the ship without appropriate handling procedures.